2022
DOI: 10.3389/fphys.2022.1066455
|View full text |Cite
|
Sign up to set email alerts
|

Non-psychotropic phytocannabinoid interactions with voltage-gated sodium channels: An update on cannabidiol and cannabigerol

Abstract: Phytocannabinoids, found in the plant, Cannabis sativa, are an important class of natural compounds with physiological effects. These compounds can be generally divided into two classes: psychoactive and non-psychoactive. Those which do not impart psychoactivity are assumed to predominantly function via endocannabinoid receptor (CB) -independent pathways and molecular targets, including other receptors and ion channels. Among these targets, the voltage-gated sodium (Nav) channels are particularly interesting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 88 publications
3
12
0
Order By: Relevance
“…Like cannabidiol (CBD) and cannabigerol (CBG), CBN has been suggested as an anti-inflammatory and analgesic agent 4 , 5 . Previous studies have reported that CBN (dosed at 1 mg/ml) can mitigate myofascial pain in rats 6 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Like cannabidiol (CBD) and cannabigerol (CBG), CBN has been suggested as an anti-inflammatory and analgesic agent 4 , 5 . Previous studies have reported that CBN (dosed at 1 mg/ml) can mitigate myofascial pain in rats 6 .…”
Section: Introductionmentioning
confidence: 99%
“…THC was first discovered to interact with these receptors 11 . Recently, other non-psychotropic phytocannabinoids, including CBD and CBG, were shown to interact with several other targets 1 , 12 , including multiple receptors, ion channels, and the cell membrane itself 4 . Like CBD and CBG 4 , CBN modulates several transient receptor potential (TRP) channels 13 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations